Diamond-shape dielectric elastomer actuator using 3D printed frame - Lim, Jun Yong (2016)
Dielectric elastomer actuators (DEAs) are capacitors that is capable of producing actuation force when electrically activated. The dielectric elastomer membrane is compressed by Maxwell stress to produce an area expansion. This motion is then utilised for actuation purpose. The amount of strain and force that can be produced by DEAs is dependent on the breakdown strength of the elastomer. DEAs are still not commercially produced due to reliability issues which cause them to have very short shelf lives. The reliability of the DEA is significantly improved by fabricating the DEA within its material limits, rupture strain and subjecting it to voltages that is within breakdown voltage. DEAs can be utilised in a wide range of configurations. This makes them versatile and allows them to be used for wide range of applications. A diamond-shaped DEA is capable of generating large output strains for a given film area due to the contribution of the entire film mass for work output. The diamond DEA is also capable of utilising multiple layers of dielectric elastomer membrane to further enhance their force capability. This report focus on designing a diamond DEA which is capable of generating large output strains and force by understanding the factors that affects its performance. The design and fabrication process is included together with the experimental testing of the diamond DEA on the amount of strain and force that is capable of being produced. Specimens makes use of 3M VHB as the dielectric elastomer membrane. A diamond frame was designed and fabricated using a 3D printed nylon. The design was adapted from previous work done and modified for compatibility with the pre-stretch of the elastomer membrane. Experiments to determine the optimum pre-stretch were conducted to measure the strain and force produced by the diamond DEA at different pre-stretch. The optimum pre-stretch was capable of producing large strains of more than 20% and force-to-weight ratio of up to 13. This report shows that large output strain as well as large force-to-weight ratio is capable of being produced by diamond DEAs. Further work includes utilising multiple layers of elastomer on the diamond frame design used in this report and reducing the size of the actuator for applications in micro-robots.